2016
DOI: 10.3109/02713683.2016.1156133
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Effects of Intraocular Lens Material on Lens Epithelial Cell Proliferation, Migration, and Transformation

Abstract: Taken together, these data suggest that IOL composition greatly affects lens cell behavior during PCO development, and it appears that hydrophobic IOLs may be the best option to limit the effects of PCO after cataract surgery while also correcting the patient's vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The in vitro TM cell motility was using a scratch assay with a minor modification 27 . In brief, 2×10 5 of primary TM cells were seeded into each well of a six-well plate and cultured in an environmental chamber that was equipped with a digital camera and image acquisition software.…”
Section: Tm Motility Assaymentioning
confidence: 99%
“…The in vitro TM cell motility was using a scratch assay with a minor modification 27 . In brief, 2×10 5 of primary TM cells were seeded into each well of a six-well plate and cultured in an environmental chamber that was equipped with a digital camera and image acquisition software.…”
Section: Tm Motility Assaymentioning
confidence: 99%
“…High glucose-induced oxidative stress is an important cause of diabetic cataract [2]. The human lens epithelial cell line (HLEB3) was widely used to do research [13][14][15]. Here, using the lens epithelial cell line, we found that high glucose can directly induce the oxidative stress and cell apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…The IOL material influences the PCO changes after cataract surgery and can affect the behaviour of LECs. 8,14 The exact mechanism is unknown but could be explained by either mechanical or material related effects.…”
Section: Discussionmentioning
confidence: 99%